Applications of Reference Materials in Analytical Chemistry. - Walker, Ron (Valid Analytical Measurement., 2001)
Reference materials play an important role in analytical chemistry, where they are used by analysts for a variety of purposes, including: checking and calibrating instruments; validating methods and estimating the uncertainty of analytical measurements; checking laboratory and analyst performance; and internal quality control. This book provides guidance and information for the users of certified reference materials (CRMs), explaining how they can best be used to achieve valid analytical measurements and improve quality in the analytical laboratory. General information on CRMs and how they are.